Integration of patient‐reported outcome measures with key clinical outcomes after immediate latissimus dorsi breast reconstruction and adjuvant treatment. Issue 2 (22nd November 2012) - Winters, Z. E.; Haviland, J.; Balta, V.; Benson, J.; Reece‐Smith, A.; Betambeau, N.; ,
Abstract Background: Clinical evidence on patient‐reported outcome measures (PROMS) in breast reconstruction is lacking. The aim of this study was to evaluate PROMs in implant‐assisted latissimus dorsi (LDI) or tissue‐only autologous latissimus dorsi (ALD) flap reconstruction in relation to complications and adjuvant treatments. Methods: This was a prospective cohort study involving six UK centres. Eligible patients had primary early‐stage breast cancer. The European Organization for Research and Treatment of Cancer quality‐of‐life questionnaire (QLQ)‐C30 and QLQ‐BR23, Functional Assessment of Cancer Therapy—Breast Cancer scale (FACT‐B), Body Image Scale, and Hospital Anxiety and Depression Scale were completed before operation and at 3, 6 and 12 months after surgery. Results: A total of 182 patients (82 LDI and 100 ALD) were recruited between 2007 and 2010 with symptomatic (59·9 per cent) or screen‐detected (39·6 per cent) cancers. Some 64·3 per cent had lymph node‐negative disease; 30 per cent of the LDI group had radiotherapy, compared with 53·0 per cent in the ALD group (P = 0·004). Early complications up to 3 months after surgery were reported in 66 and 51·0 per cent of patients in the LDI and ALD groups respectively (P = 0·062) and long‐term complications (4–12 months) in 48 and 45·0 per cent (P = 0·845). Role functioning and pain (P = 0·002 for both) were adversely affected in the ALD group compared with results in the LDI group, with no significant effects of radiotherapy on any health‐related quality of life (HRQL). Chemotherapy and early complications adversely affected HRQL, which improved between 3 and 12 months after surgery (P < 0·010 for all). Conclusion: There is evidence of similar HRQL between types of latissimus dorsi breast reconstruction for up to a year after surgery. There appear to be no overarching effects for radiotherapy after mastectomy on the specific HRQL domains studied in the short term. The identification of variables that affect HRQL is important, including their integration into the analysis of PROMs. Copyright © 2012 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd.